Using IgY for diagnosis of respiratory infections: practical application in COVID-19 - Cícero Matheus Lima Amaral; Valdester Cavalcante Pinto Júnior; Daniel Freire Lima; Hellen paula Silva da Costa; Danúbio Andrade Bezerra Farias; João Xavier da Silva Neto; Luiz Francisco Wemmenson Gonçalves Moura; Bruno Bezerra da Silva; Ednardo Rodrigues Freitas; Maurício Fraga Van Tilburg; Maria Izabel Florindo Guedes (Future Science OA)
Aim The COVID-19 pandemic underscores the need for expanded diagnostic tools to combat respiratory pathogens with pandemic potential, particularly in developing countries. This study aimed to create a Dot Blotting test utilizing IgY antibodies for acute respiratory infection diagnosis, with COVID-19 as the disease model.Methods Leghorn chickens were immunized with precipitated SARS-CoV-2 virus, and IgY antibodies were purified via ammonium sulfate precipitation and titrated by ELISA. Dot Blotting detected viral antigens in saliva samples, demonstrating efficacy comparable to ELISA tests.Results The IgY antibody was successfully produced and purified, obtaining a titration of 1:16,000. The ability of IgY to detect SARS-CoV-2 in clinical saliva samples showed promising results in terms of accuracy (91.3%), sensitivity (92.5%), specificity (90.0%), positive predictive value (PPV) (90.2%), negative predictive value (NPV) (92.3%), and Cohen’s Kappa (0.825).Conclusion Chicken antibodies proved effective for early and accurate diagnosis of respiratory infections, including COVID-19. This study validates the efficacy of chicken antibodies in diagnosing respiratory infections, supporting pandemic response in developing nations. Expanding diagnostic capabilities is crucial for combating respiratory pathogens.